1996
DOI: 10.1006/icar.1996.0130
|View full text |Cite
|
Sign up to set email alerts
|

Optical Effects of Regolith Processes on S-Asteroids as Simulated by Laser Shots on Ordinary Chondrite and Other Mafic Materials

Abstract: up ȁ80% of observed meteorite falls, but so far very few asteroid spectral analogs have been identified for these meLaboratory results from a simulation of possible optical effects of impact melting and repeated crystallization on asteroi-teorites. dal surfaces are presented. Quick melting and crystallizationThe S-asteroids are widespread in the inner belt and of surface materials were simulated by impulse laser treatment appear to consist mostly of olivine, orthopyroxene, and of powdered materials in vacuum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 22 publications
3
90
2
1
Order By: Relevance
“…In particular, a study by Moroz et al (1996) showed that weak irradiation of a carbonaceous chondrite led to a blueing of the spectrum. With higher irradiation doses, they found a reddening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a study by Moroz et al (1996) showed that weak irradiation of a carbonaceous chondrite led to a blueing of the spectrum. With higher irradiation doses, they found a reddening.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, low dose laser irradiation of the carbonaceous meteorite Allende initially results in blueing. However, after an increased dose of laser irradiation, Moroz et al (1996) found that the spectrum reddens. Studying color variations between young and old asteroids families, Nesvorny et al (2005) found that aging surfaces of S-type become increasingly redder and that aging surfaces of C-type asteroids become increasingly bluer.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Meteorite regolith breccias, as proxies for asteroidal regolith, were searched for similar nanophase particles, with the howardite Kapoeta being one of the few minor, but successful detections (Noble et al 2010). Laboratory experiments have various degrees of success in simulating these particular space weathering products along with their optical effects (e.g., Cassidy and Hapke 1975;Moroz et al 1996;Yamada et al 1999;. A model describing the optical effects of nanophase metallic iron was successfully developed by Hapke (2001).…”
Section: Spwe: Backgroundmentioning
confidence: 99%
“…These spectral changes are attributed to the vapor deposition of sub-micron metallic iron (SMFe) particles onto grains during micrometeorite impacts and solar wind irradiation (Yamada et al 1999;Hapke 2001;Sasaki et al 2001;Brunetto & Strazzulla 2005). The intrinsically dark (p v ∼0.06; Mainzer et al 2011) nature of carbonaceous material and the lack of prominent absorption features at visible and near-IR wavelengths implied space weathering trends would be difficult to identify for C-complex asteroids (Hapke 2001;Moroz et al 1996). However, two recent studies indicate significant spectral slope variation among this class of asteroids as a function of age (Nesvorný et al 2005;Lazzarin et al 2006).…”
Section: Introductionmentioning
confidence: 99%